Generation of a Single-Cell RNAseq Atlas of Murine Salivary Gland Development - Belinda R. Hauser; Marit H. Aure; Michael C. Kelly; Matthew P. Hoffman; Alejandro M. Chibly (iScience, 2020)
Summary: Understanding the dynamic transcriptional landscape throughout organ development will provide a template for regenerative therapies. Here, we generated a single-cell RNA sequencing atlas of murine submandibular glands identifying transcriptional profiles that revealed cellular heterogeneity during landmark developmental events: end bud formation, branching morphogenesis, cytodifferentiation, maturation, and homeostasis. Trajectory inference analysis suggests plasticity among acinar and duct populations. We identify transcription factors correlated with acinar differentiation including Spdef, Etv1, and Xbp1, and loss of Ybx1, Eno1, Sox11, and Atf4. Furthermore, we characterize two intercalated duct populations defined by either Gfra3 and Kit, or Gstt1. This atlas can be used to investigate specific cell functions and comparative studies predicting common mechanisms involved in development of branching organs.